2019
DOI: 10.3389/fmicb.2019.01238
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis: Plant Friend or Foe in the Fight Against Viruses?

Abstract: Plant roots establish interactions with several beneficial soil microorganisms including arbuscular mycorrhizal fungi (AMF). In addition to promoting plant nutrition and growth, AMF colonization can prime systemic plant defense and enhance tolerance to a wide range of environmental stresses and below-ground pathogens. A protective effect of the AMF against above-ground pathogens has also been described in different plant species, but it seems to largely rely on the type of attacker. Viruses are obligate biotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 64 publications
4
44
1
2
Order By: Relevance
“…Our results are consistent with those of [ 37 ] showing a reduction in viral symptoms in mycorrhizal tomato plants infected by tomato yellow leaf curl Sardinia virus (a DNA virus) when compared with those infected but not mycorrhized. However, our results are in contrast with those reported by other studies, performed on different RNA viruses, highlighting that the AMF colonization may lead to a worsening of symptoms and to an increase of viral titer over time [ 34 , 35 , 52 , 53 ]. Overall, these data suggest that the mycorrhization interferes with dynamics of viral infection and symptomatology in a way that likely depends on the specific combination of virus and plant species involved.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Our results are consistent with those of [ 37 ] showing a reduction in viral symptoms in mycorrhizal tomato plants infected by tomato yellow leaf curl Sardinia virus (a DNA virus) when compared with those infected but not mycorrhized. However, our results are in contrast with those reported by other studies, performed on different RNA viruses, highlighting that the AMF colonization may lead to a worsening of symptoms and to an increase of viral titer over time [ 34 , 35 , 52 , 53 ]. Overall, these data suggest that the mycorrhization interferes with dynamics of viral infection and symptomatology in a way that likely depends on the specific combination of virus and plant species involved.…”
Section: Discussioncontrasting
confidence: 99%
“…Although AMF colonization has been already shown to decrease the severity of diseases caused by several plant pathogens [ 24 ], the effects of AMF on plant–virus interaction have received limited consideration and are not yet fully understood. The final outcome of a plant–AMF–virus tripartite interaction relies on several factors, including viral pathogen lifestyle, nutritional status of the plant, and timing of interaction [ 35 ]. The term “mycorrhiza-induced susceptibility” (MIS) has been proposed for the cases where AMF colonization increases the susceptibility of plants to viruses [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, results from this study and other studies on the interaction of plant-virus and AM fungi [ 43 , 44 , 45 ] show a differential effect for AM fungi on plant virus disease development. We found that mycorrhizal symbiosis has a positive effect on tomato plant resistance to TBSV.…”
Section: Discussionsupporting
confidence: 67%
“…The benefits of AMF symbiosis to plants may arise from a combination of increased plant biomass and reprogrammed plant primary and secondary metabolome. However, studies have also found alternate results in which AMF association makes the plant vulnerable against pathogens [ 185 ] and decreases the biomass of the plants [ 35 ]. The outcome of the plant–AMF symbiosis is highly species-specific, where some AMF associations result in a positive outcome, while others exhibit neutral or negative outcomes (parasitism; [ 35 ]).…”
Section: Resultsmentioning
confidence: 99%